Cohort profile: social well-being and determinants of health study (SWADES), Kerala, India - Saju M D; Lovakanth Nukala; Rameela Shekhar; Keith Gomez; Bindiya M Varghese; Anuja Maria Benny; Lorane Scaria; Sphoorthi Prabhu; Amuthavalli Thiyagarajan Jotheeswaran (BMJ Open)
Purpose In response to the need for more advanced and longitudinal data concerning chronic diseases, behavioural risk factors and social support systems in India, the SWADES (Social Well-being and Determinants of Health Study) was established.Participants At baseline, 997 adults aged 30 years and over, living in the semi-urban area were interviewed in their home.Findings to date Data collected included self-reports of demographic details, health, depression, morbid conditions and healthcare utilisation, risk factors (physical, behavioural and social) of chronic diseases, common mental disorders, out-of-pocket expenditure, social support network, social cohesion, disability, education and wealth. Objective data for hypertension, diabetes and cognitive function were also collected.Future plans The first annual follow-up interviews were completed in 2019; the subsequent annual follow-up will be conducted until 2030. The SWADES data are held at the International Centre for Consortium Research in Social Care (ICRS), Rajagiri College of Social Science, Kerala, India. Procedures for data access, information on collaborations, publications and other details can be found at (http://icrs.in).